2017
DOI: 10.1111/nmo.13184
|View full text |Cite
|
Sign up to set email alerts
|

Sacral nerve stimulation for constipation and fecal incontinence in children: Long‐term outcomes, patient benefit, and parent satisfaction

Abstract: Sacral nerve stimulation is a promising and durable treatment for children with refractory constipation, and appears particularly effective in decreasing fecal incontinence. Although a quarter of patients experienced complications requiring additional surgery, nearly all parents reported health-related benefit. Future studies to identify predictors of treatment response and complications are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…Baseline evaluation of patients was reported heterogeneously within the different papers; clinical examination, All the published studies reported a two-stage technique of implant for ISNM, as previously described. [6][7][8][9][10][11][12] The first stage is the diagnostic stage for which two possible options are available: temporary wire or tined lead. Following the testing period of generally 2 to 3 weeks, patients received the definitive implant in which the implantable stimulator was implanted.…”
Section: Results: Invasive Neuromodulation Technique-isnmmentioning
confidence: 99%
See 2 more Smart Citations
“…Baseline evaluation of patients was reported heterogeneously within the different papers; clinical examination, All the published studies reported a two-stage technique of implant for ISNM, as previously described. [6][7][8][9][10][11][12] The first stage is the diagnostic stage for which two possible options are available: temporary wire or tined lead. Following the testing period of generally 2 to 3 weeks, patients received the definitive implant in which the implantable stimulator was implanted.…”
Section: Results: Invasive Neuromodulation Technique-isnmmentioning
confidence: 99%
“…Criteria for definitive implant were more than 50% improvement in the baseline symptoms 7 and more than three time increase in defecation frequency per week. 8,9 Haddad et al 10 in their crossover study divided the patients as responders or nonresponders regarding the fecal performance; the response was defined as resolution of fecal soiling with no need for pads or a decrease of more than 50% in the numbers of leaks or soiling episodes. Overall, a positive response rate was more than 75%, indicating that neuromodulation was more effective than conservative treatment of fecal incontinence.…”
Section: Results: Invasive Neuromodulation Technique-isnmmentioning
confidence: 99%
See 1 more Smart Citation
“…One wonders, if this effect is sustained, perhaps future, adult LUTS with initial treatment in childhood could be altered or eliminated. Explant surveys for those explanted for cure and complication.^Raw scores in the cure cohort were 5,8,9,15,16. * Based upon cut-off score of 11 suggested by Afsar et al [12].…”
Section: Discussionmentioning
confidence: 99%
“…A significant improvement in symptoms and quality of life was reported at a median of 4-5 months after SNS initiation. In a follow-up study, SNS led to continued improvement in both symptoms and quality of life at 2 years after treatment initiation, with particular improvement in concurrent fecal incontinence [56]. At follow-up, 68% of patients fulfilled the predefined criteria for successful response and 24% fulfilled criteria without concurrent laxative or ACE use.…”
Section: Neuromodulationmentioning
confidence: 96%